Woman’s Language Features Used in Ted Talks - Anisa Afrillya; Andi Idayani (ELT-Lectura, 2023)
The aim of this research was to find out how the woman's language features used in Ted Talks videos and the language functions used by the woman speakers in Ted Talks. This research is descriptive. This is a descriptive study. The researcher obtained the data by downloading and writing the transcripts of Ted Talks videos. The researcher recognized the sorts of woman's language features utilized by women speakers in TED talk videos to examine the data. The study then determined the language function of all types of female language characteristics utilized by female speakers in TED talks videos. The researcher discovered that women speakers in Ted Talks employed seven sorts of female language features, such as lexical hedges or fillers, tag questions, rising intonation on declaratives, empty adjectives, intensifiers, hypercorrect grammar, and super polite forms, as the study's final conclusion. The researchers also discovered the language functions employed by women speakers in Ted Talk, such as directive, expressive, referential, metalinguistic, and phatic. However, the researcher found no language features or functions exclusive to women that were not employed by women speakers in Ted Talks, such as exact color descriptors, avoidance of harsh swear words, and emphatic stress. The poetic function is a language function that women speakers in Ted Talks do not employ.